AWARENESS AND ADOPTION OF MAINTAINING QUALITY STANDARDS: A CONFECTIONERIES PRODUCERS’ PROSPECTIVE - Sandika, AL; Seethagama, SP; Jayamanne, VS (European Scientific Journal, ESJ, 2014)
Confectionary sector is one of major sub sector of Sri Lankan food marketing. But, many occasions, consumers ignore the food quality information due to lack of awareness. Quality is becoming increasingly important to all entrepreneurs. Therefore, this study was conducted to identify the producers’ awareness and adoption towards maintaining of food quality standards. Beliatta DS division was selected purposively as study area of this investigation. Randomly selected 40 producers were used in order to find out the relevant information such as awareness and adoption towards maintaining of food quality standards. Primary data was collected through pre tested interview schedules with the systematic observation. Significant numbers of producers’ were not aware about quality standards viz, SLS, ISO or HACCP. Fateful condition was that they did not know even the name of the quality standards. However, 68% of producers were aware about GMP because they had participated to training programme which were organized by Vidatha centers and Industrial Development Board. They were further encouraged to fulfill the GMP practices in their production line. Further, producers’ attempts to maintain the GMP was observed as very low due to producers’ negative attitudes and negligence, lack of skill and low investment ability etc. Therefore, relevant private and public institutes have to pay grate attention on this matter, and also they should give their service to improve the quality standards of the confectionary food sector.